Discrimination on the Right to Get Salary for Women Workers in Indonesia from the Ratification of International Conventions Perspective - Ni Ketut Sari Adnyani; I Wayan Landrawan (Pandecta Research Law Journal, 2023)
Discrimination against women workers is a violation of human rights as regulated in international instruments such as the International Labor Organization ILO and CEDAW. Constitutionally, the rights of every Indonesian citizen are based on Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Protection of workers is also regulated in Law Number 13 of 2003 concerning Manpower Articles 67 to Article 101 which cover the protection of safety, health and welfare assurance. However, not many women themselves realize that their rights are protected and this has an impact on women’s lives. Reviewing arrangements for the rights of women workers regulated in the ILO, CEDAW and Manpower and their implementing regulations. Accommodate a number of related regulations above, based on gender responsiveness for female workers. This study aims to examine how the accommodation of international conventions into Indonesian positive law? and efforts to strengthen the implementation of the convention?. Types of normative research. The results of this study indicate that there are protection arrangements in conventions that can be adopted. In the future, editorial guarantees for protection for women will be prepared.